(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Physical inactivity in children remains a significant public health issue, with nearly 40% of United Kingdom children aged 8–10 not meeting recommended activity levels. While many interventions exist, a persistent gap remains – those children who remain inactive despite these efforts. This study aimed to co-develop a set of evidence-informed design principles specifically for interventions targeting the least active 8–10-year-olds. By using a stakeholder-led process, the goal was to generate practical, context-sensitive strategies that can be applied in both school and community settings. Methods: This qualitative research followed the Double Diamond Design Approach (DDDA) through a structured co-development workshop using participatory methods. Stakeholders (n = 29), including researchers (n = 12), public health professionals (n = 7), and community practitioners (n = 10), were recruited to ensure varied perspectives. Written and verbal data were collected through audio-recorded group discussions and workshops. Results: Preliminary insights included key themes relating to whole-family engagement, early years inclusion, and reframing physical activity as ‘movement’ to enhance accessibility and reduce stigma. Stakeholders prioritised culturally sensitive, inclusive designs and emphasised the importance of unstructured, fun-based play. Hyper-local delivery, safe environments, and adaptable programming were also highlighted as essential. Creative and multisport options, workforce diversity, and peer leadership also featured strongly. A modified Delphi process will be used for stakeholders to review and provide feedback on the draft principles. The final principles and statements will be presented at the HEPA conference. Conclusion: This study highlights the value of structured co-development in generating context-specific, practical strategies to increase physical activity among the least active children. By integrating stakeholder expertise with child- and parent-centred insights, the guiding principles developed are grounded in lived experience and designed for implementation in both school and community settings. The findings offer actionable, scalable solutions for educators, practitioners, and policymakers aiming to address persistent physical activity inequalities. Ongoing refinement further strengthens these principles, with future phases focused on real-world piloting to assess feasibility, sustainability, and long-term impact. ​Support/Funding Source: PhD funded through White Rose Doctoral Training Partnership.